The Spatiotemporal Deposition of Lysophosphatidylcholine Within Starch Granules of Maize Endosperm and its Relationships to the Expression of Genes Involved in Endoplasmic Reticulum–Amyloplast Lipid Trafficking and Galactolipid Synthesis. (6th October 2018) - Gayral, Mathieu; Fanuel, Mathieu; Rogniaux, Hlne; Dalgalarrondo, Michle; Elmorjani, Khalil; Bakan, Bndicte; Marion, Didier
Abstract: The presence of lipids within starch granules is specific to cereal endosperm starches. These starch lipids are composed of lysophospholipids, especially lysophosphatidylcholine (LysoPC) and free fatty acids that strongly impact the assembly and properties of cereal starches. However, the molecular mechanisms associated with this specific lipid routing have never been investigated. In this study, matrix-assisted laser desorption ionization mass spectrometry imaging revealed decreasing gradients in starch LysoPC concentrations from the periphery to the center of developing maize endosperms. This spatiotemporal deposition of starch LysoPC was similar to that previously observed for endoplasmic reticulum (ER)-synthesized storage proteins, i.e. zeins, suggesting that LysoPC might originate in the ER, as already reported for chloroplasts. Furthermore, a decrease of the palmitate concentration of amyloplast galactolipids was observed during endosperm development, correlated with the preferential trapping of palmitoyl-LysoPC by starch carbohydrates, suggesting a link between LysoPC and galactolipid synthesis. Using microarray, the homologous genes of the Arabidopsis ER–chloroplast lipid trafficking and galactolipid synthesis pathways were also expressed in maize endosperm. These strong similarities suggest that the encoded enzymes and transporters are adapted to managing the differences between chloroplast and amyloplast lipid homeostasis. Altogether, our results led us to propose a model where ER–amyloplast lipid trafficking directs the LysoPC towards one of two routes, the first towards the stroma and starch granules and the other towards galactolipid synthesis.